Rozdźwięk między administracją partyjno-państwową a społeczeństwem na tle katechizacji szkolnej w osadzie wiejskiej Czerwieńsk w powiecie zielonogórskim w latach 1952-1956 = The dissonance between the party-national administration and society against religious education in rural settlement of Czerwieńsk in Zielona Góra poviat, 1952-1956 - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 1955 with the beginning of the ministry in the parish dedicated to St Adalbert in Czerwieńsk by priest Stanisław Stępień from his initiative, despite surveillance and insults from the safety apparatus, he succeeded in encouraging the believers to be more active, especially in 1956. His activity was focused on propagation of the ideas of the Catholic Church among their children who were taught in the local primary school. It was women who played the key role in these efforts and who led to the decisive meeting of the parents` committee which was held at the end of September 1956.
Keywords: stosunki państwo-kościół; Ziemie Zachodnie i Północne; Czerwieńsk; Polska - historia - od 1944 r.